Mesophase pitch-based graphite fiber-reinforced acrylonitrile butadiene styrene resin composites with high thermal conductivity. (December 2015) - Yuan, Guanming; Li, Xuanke; Yi, Jing; Dong, Zhijun; Westwood, Aidan; Li, Baoliu; Cui, Zhengwei; Cong, Ye; Zhang, Jiang; Li, Yanjun
Abstract: One-dimensional (1-D) and two-dimensional (2-D) mesophase pitch-based graphite fiber (MPGF)/acrylonitrile butadiene styrene (ABS) resin composites were prepared from unidirectionally arranged MPGF/ABS resin laminae by a hot-press method. The morphologies, optical texture and crystal structure of the MPGFs and their ABS resin composites were investigated. The influence of the volume fraction, diameter and graphitization temperature of the MPGFs and the composite architecture on the thermal properties of the composites was discussed. The thermal diffusivity and thermal conductivity of the resultant composites parallel to the longitudinal fiber direction increase markedly with the volume fraction, diameter and graphitization temperature of the fibers. The 1-D composite with a fiber volume fraction of 62% possesses a bulk density of 1.64 g/cm 3 and shows a high thermal diffusivity of 372 mm 2 /s and a high thermal conductivity of 518 W/m K parallel to the longitudinal fiber direction at room temperature. The corresponding axial thermal conductivity of the fibers, graphitized at 2900 °C with a diameter of 50–55 μm, is estimated to be 825 W/m K. The 2-D composite filled with a high (54%) volume fraction of MPGFs also exhibits a high thermal conductivity in two directions (parallel to the longitudinal directions of the incorporated fibers).